Global epidemiology of campylobacteriosis and the impact of COVID-19 - Liu, Fang; Lee, Seul A.; Xue, Jessica; Riordan, Stephen M.; Zhang, Li (Frontiers in Cellular and Infection Microbiology, 2022)
Campylobacteriosis is a gastroenteritis caused by pathogenic Campylobacter species and an important topic in public health. Here we review the global epidemiology of campylobacteriosis in the last eight years between 2014-2021, providing comprehensive and updated information on the reported incidence and outbreaks of Campylobacter infections. The government public health website of each of the 195 countries and publications from 2014 to September 2022 in public databases were searched. The reported incidence of campylobacteriosis in pre-COVID-19 years was compared to that during the COVID-19 pandemic in countries where data were available. Czech Republic had the highest reported incidence of campylobacteriosis worldwide (215 per 100,000 in 2019), followed by Australia (146.8 per 100,000 in 2016) and New Zealand (126.1 per 100,000 in 2019). Campylobacter was one of the most common human enteric pathogens in both developed and developing countries. About 90% of cases of campylobacteriosis were caused by Campylobacter jejuni, whereas less than 10% of cases were caused by Campylobacter coli. Other Campylobacter species were also isolated. The reported incidence and case numbers of campylobacteriosis in developed nations have remained steadily high prior to the COVID-19 pandemic, whilst some countries reported an increasing trend such as France and Japan. While outbreaks were more frequently reported in some countries, Campylobacter infections were mainly sporadic cases in most of the developed countries. Campylobacter infection was more common in summer in some but not all countries. Campylobacter infection was more common in males than females. The COVID-19 pandemic has reduced the reported incidence of campylobacteriosis in most countries where 2020 epidemiology data were available. In conclusion, Campylobacter infection remains a global health concern. Increased research and improved strategies are needed for prevention and reduction of Campylobacter infection.